Nuova testimonianza dell’uso delle terrecotte nel culto del Foro Triangolare a Pompei - Kappe, Constantin; Giletti, Federico (O T I V M, 2024)
In 2015 the Archaeological Park of Pompei and Naples University Federico II started new investigations in the Athena sanctuary (Triangular Forum). This paper discusses a votive deposit which came to light during the 2019 campaign in the north-eastern sector of the sanctuary. The essay seeks to contextualize the formation of the assemblage comprehensively within the wider transformation processes taking place in the sanctuary in the late 2nd century BC. The coroplastic material is studied from a typological and iconographic perspective, giving new insight into the cult practices that are probably connected with prenuptial rituals.